Kajian nilai manfaat langsung ekosistem mangrove di Desa Moko Kecamatan Lakudo Kabupaten Buton Tengah Sulawesi Tenggara - Rosmawati; Haris, Abdul; Nurdiana A; Piliana, Wa Ode; Hamzah, Muhaimin; Sidiq, Azwar (Jurnal Sosial Ekonomi Perikanan, 2023)
Mangroves are one of the coastal ecosystems with various ecosystem services include economic benefits. The purpose of this study is to determine the economic value of mangrove ecosystems that are directly utilized by the people of Moko Village, Lakudo District, Central Buton Regency, Southeast Sulawesi. This research was conducted during the period from August to September 2021. The sampling method used was the accidental sampling method, which is a non-probability sampling technique by determining the sample based on who was encountered at the time of data collection. The research sample was the people of Moko Village who live around the mangroves and directly use of the products from the mangrove forest. The types of data used were primary data and secondary data that are qualitative and quantitative. Primary data were obtained directly from the field through interviews with related parties, questionnaires, and direct observation. Secondary data were obtained from the Tourism Office of Central Buton Regency and through literature studies that related to research aims The results of this study showed that the benefits of the mangrove ecosystem in Moko Village consisted of fishing, crab, and shrimp fishing around and in the mangrove forest. The annual total benefit value of mangroves was IDR.507,704,732,- which consisted of fish benefits of IDR 149,064,333,- crab benefits of IDR .230,170,566,- and shrimp benefits of IDR.128,469,833,-.